Study of Production and Marketing Subsystem in Private Forest Development KAJIAN SUBSISTEM PRODUKSI DAN PEMASARAN DALAM PENGEMBANGAN HUTAN RAKYAT - Andy Risasmoko; Hardjanto .; Leti Sundawati (Jurnal Silvikultur Tropika, 2016)
Private forest has benefit of economic, ecology, and social. Private forest development need to be conducted continuously to gain the optimal benefit. In developing of private forest need to understanding of private forest management system, i.e. production and marketing subsystem. This research was conducted in Glontor Village and Tlogosari Village, Kebumen District by purposive sampling method within 60 farmers as respondent. The objectives of this research are to analyze the production and marketing subsystem of private forest. Data collected by observation, interview, and literature study. Result of research showed that production subsystem: private property land, private forest development more conducted in mountainous area, most of cropping are agroforestry and mixed planting, plant maintenance have not been conducted intensively. Marketing subsystem: the middleman played a major role in the marketing of timber, purchasing on standing stock, and farmer as price taker.Key words: marketing subsystem, private forest development, production subsystem